Elevating Factors Obedience Nurse in Application Principle Six Correct Giving Drug: Literature Reviews - Ayu Sri Wahyuni; Suradi Efendi; Nour Sriyanah (International Journal of Public Health Excellence (IJPHE), 2023)
Nurse as direct officer give service to patient, expected capable develop and maintain procedure gift safe drug to use give service and protection best for patient. Objective studies literature This that is identify enhancing factor obedience nurse in application principle six Correct gift medicine. Method writing used namely Systematic Literature Review for browse various enhancing factor obedience nurse in gift medicine. Data retrieved is article around six correct principle gift drugs and enhancing factors obedience nurse. Literature from source Trusted in English and Indonesian with range publication 2004-2019. Collected data appropriate critical appraisal tool is carried out with desired goal achieved to 9. The results of the review show there is a number of factor related obedience nurse in gift drug that is good knowledge and attitude, existence of SOP and policies, burden no work too excessive as well as working nurse it's been a while. Study conclusion literature This that is possible factor increase obedience nurse in application principle six Correct gift drug is level knowledge, attitude, availability of SOP, load work and length of work nurse.